Democracies cooperate more: even where it threatens to bite?. Issue 11 (23rd July 2016) - Hühne, Philipp; Meyer, Birgit; Nunnenkamp, Peter; Roy, Martin
ABSTRACT: Estimating two-step selection models, we find that more democratic governments are more likely to conclude preferential trade agreements (PTAs) and to agree to stricter investment provisions related to pre-establishment national treatment and investor–state dispute settlement in PTAs. This is surprising when considering the potentially high costs of litigation.